New Business Strategy to Get More SMEs as Customers: Case of PT. XL AXIATA Tbk - Ihsan, Muhammad; Dung DO, Anh (The Indonesian Journal of Business Administration, 2019)
Abstract. This research will analyze a business case of PT. XL Axiata Tbk. (XL), a mobile telecommunication operator, with specific focus on penetration market of the SMEs to get more new subscribers. Therefore, the objective of writing the paper is to identify how XL could possibly increase new subscribers of SMEs through business strategy formulation and new business model generation for XL in order to achieve sustainable competitive advantage. In order to achieve the research objectives, the data has been collected from literature study and conducted interview session with 37 SMEs. With that data, conduct further analysis using environment analysis, strategy formulation, business model and implementations plans. Based on analysis of data that has been collected, some key points that capture that the actor of SME is in millennial age which more adaptable possibility with new technology and product that offered. Digitalization should be an alternative to offer to them, such platform with integrated system to the digital media, third party system (delivery, packaging), cloud system that can be used to record any transaction, stock list. And the interested thing that the SME need capital loan which can be provided by XL.  Keywords:  business strategy, business formulation, small medium enterprise, focus strategy.